Energy cost and energy sources of an elite female soccer player to repeated sprint ability test: A case study - Perroni, F.; Emerenziani, G. P.; Pentenè, F.; Gallotta, M. C.; Guidetti, L.; Baldari, C. (Preprints, 2018)
Intense physical efforts performed at maximal or near-maximal speeds and the ability to recover among sprint are important characteristics of soccer player. Considering that women's soccer is a markedly growing sport, the aim of the study was to analyse the performance (total time -TT-; fatigue index percentage -IF%) and physiological (aerobic and anaerobic) responses to Repeated Sprint Ability Test (RSA, 7×30 m sprints with 25 s of active recovery among sprints) in an elite female player (age: 30 yrs; BMI: 20.3 kg/m2). A repeated measure MANOVA over the 7 sprints time series was applied (p < 0.05). Results showed that TT was 58.71 s (Ideal Time: 56.98 s) with IF% of 3.0%. Energy contributions were given for 80.3% by aerobic, 19.2% by anaerobic lactid, and 0.5% by anaerobic alactid sources. Considering that 1) we have different kinetics in heart rate (HR) and maximum oxygen uptake with oxygen uptake that reach the peak when HR is still rising, and 2) the energy consumption during intermittent exercises requires different metabolism as a result of physiological stimuli proposed, the present findings substantiate the need to choose specific and adequate training methods for female soccer players that aim at increasing their RSA performances.